Invariant symmetric restrictions of a self-adjoint operator. I - Dudkin, M. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove necessary and sufficient conditions of the S-invariance of a subset dense in a separable Hilbert space H.